2023
DOI: 10.3390/v15051209
|View full text |Cite
|
Sign up to set email alerts
|

Area Wide Monitoring of Plant and Honey Bee (Apis mellifera) Viruses in Blueberry (Vaccinium corymbosum) Agroecosystems Facilitated by Honey Bee Pollination

Eunseo Lee,
Raj Vansia,
James Phelan
et al.

Abstract: Healthy agroecosystems are dependent on a complex web of factors and inter-species interactions. Flowers are hubs for pathogen transmission, including the horizontal or vertical transmission of plant-viruses and the horizontal transmission of bee-viruses. Pollination by the European honey bee (Apis mellifera) is critical for industrial fruit production, but bees can also vector viruses and other pathogens between individuals. Here, we utilized commercial honey bee pollination services in blueberry (Vaccinium c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 78 publications
0
12
0
Order By: Relevance
“…Plant-infecting viruses are a serious threat to food security globally. While in their infancy, approaches that seek to indirectly sample viruses that likely infect plants via the sampling of common pollinators have been investigated [ 9 , 10 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 61 ]. This effort has mainly focused on plant-infecting RNA viruses using targeted and non-targeted assays.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant-infecting viruses are a serious threat to food security globally. While in their infancy, approaches that seek to indirectly sample viruses that likely infect plants via the sampling of common pollinators have been investigated [ 9 , 10 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 61 ]. This effort has mainly focused on plant-infecting RNA viruses using targeted and non-targeted assays.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, bees can be useful surveillance tools for plant-infecting viruses, especially those that are pollen-associated [ 29 , 30 , 31 ]. Plant-infecting RNA viruses in the families Alphaflexiviridae , Amalgaviridae , Aspiviridae , Betaflexiviridae , Bromoviridae , Chrysoviridae , Luteoviridae , Mayoviridae , Partitiviridae , Phenuiviridae , Potyviridae , Secoviridae , Solemoviridae , Tombusviridae , Tymoviridae, and Virgaviridae have been found in honeybees or in pollen on honeybees [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ]. On the other hand, little is known about plant-infecting DNA viruses in honeybees and only two reports have identified geminiviruses (genus begomovirus ) in stingless bees ( Trigona spp.)…”
Section: Introductionmentioning
confidence: 99%
“…Given the complexity and large number of viruses present in mixed apple and cherry production systems, large scale area-wide monitoring approaches could be beneficial in understanding the diversity of pathogens present, and identifying priorities for management ( Roberts et al., 2023 ). Bee-mediated pollen collection, combined with metagenomic sequencing approaches is a powerful emerging tool in biovigilance and pathogen monitoring ( Roberts et al., 2018 ; Beaver-Kanuya and Harper, 2019 ; Tremblay et al., 2019 ; Cunningham et al., 2022 ; Lee et al., 2023 ; Tayal et al., 2023 ). Bee foraging activities essentially sample small amounts of pollen and nectar from multiple flowering individuals within a radius of approximately 2 kilometres from their colony ( Steffan-Dewenter and Kuhn, 2003 ; Couvillon et al., 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Bee foraging activities essentially sample small amounts of pollen and nectar from multiple flowering individuals within a radius of approximately 2 kilometres from their colony ( Steffan-Dewenter and Kuhn, 2003 ; Couvillon et al., 2014 ). Many viruses are associated with pollen or bees, and detectable through metagenomics approaches ( Card et al., 2007 ; Pallas et al., 2012 ; Roberts et al., 2018 ; Fetters et al., 2022 ; Fetters and Ashman, 2023 ; Lee et al., 2023 ). Here we report the identification of multiple virus species in bee and pollen samples collected from three apple and three cherry sites in Creston valley, BC through bee-mediated metagenomics.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanically transmitted viruses are sometimes transmitted by non-host vectors, primarily via mechanical adherence. Bee colonies were considered vectors of plant viruses [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ], and metagenomics studies of bee populations were found to be beneficial in the identification of plant viruses in various ecosystems [ 16 , 17 , 18 , 19 , 20 , 21 ]. The ability to share viruses between managed and wild bees [ 22 , 23 ] may lead to a wide plant virus spread within a specific geographic region [ 18 ].…”
Section: Introductionmentioning
confidence: 99%